Polyacrylamide-Entrapped Rhizobium as an Inoculant for Legumes - Dommergues, Y. R. (1979)
Pot experiments showed that Rhizobium japonicum cells entrapped in a polyacrylamide gel could be used as an inoculant for soybeans and compared favorably to laboratory-made peat base inoculant containing the same bacterial strain.